The Effect of Textbook Readability on Students’ Reading Comprehension - Dinar Vincy Yunitaka Bahrudin (Wacana Didaktika, 2016)
Language learners should learn reading skill as one of four language skills. It is to make learners' ability on foreign language becomes more comprehensive. The purpose of reading is to improve the understanding about the content of the text and it is the central purpose of language learners. Text readability level is also influenced by the readers’ motivation, ability, and interest. Thats whay in selecting reading texts, the teacher should concern to text readability level and the student language level. Students' level must be related with text readability level, so that it is inappropriate to give junior high school students difficult text such as a difficult scientific text. Therefore this study conclude that the is an effect of textbook readability on students reading comprehension.